Desalination in Spain. Past, present and future. Issue 1 (1st February 2019) - Cabrera, E.; Estrela, T.; Lora, J.
Abstract : A summary of the evolution of desalination in Spain, spanning over half a century of history, follows. What started as a solution to resolve occasional water shortages in islands where natural surface and ground water resources were scarce, has gained more relevance with technological advancements, less expensive production costs and at the same time minimizing the impact on the environment. But fifteen years ago, the normal pace of history underwent an about-turn with the sudden construction of a significant number of desalination plants. The speed, and on occasions the haste, involved in many of the decisions, brought about some imbalance between the different players that were involved. Time, and above all, technological advancement have clarified the situation, and most of the desalination plants that were built have managed to find their place, thus justifying the investment that was made. But there are still some stages to address, particularly that of integrating these plants in the joint water resource operation systems. In this regard, consumers must accept that desalination plants competing with traditional water resources, greatly improve the guarantee of supply, and in fact act as a new water insurance that, indeed, has a cost. Today however, and particularly in the future, desalination in Spain plays and will continue to play an essential role, especially in the southeast Mediterranean region and in some of the more touristic islands. The following is a brief history.